Multistep approach for control of postpartum hemorrhage in placenta accreta: a novel scheme in a tertiary referral center - El-Agwany, Ahmed Samy; Abdeldayem, Tamer Mamdouh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Placenta accreta is a major cause for massive postpartum hemorrhage and consequent obstetric hysterectomy. Incidence is rising secondary to increased rates of caesarian delivery worldwide. Methods: From January 2014 to January 2016, 25 women with anterior low-lying placenta and previous caesarian section(s) were recruited at El-Shatby Maternity university hospital in Alexandria, Egypt. Cases had previous 1-4 lower segment caesarian deliveries. Cases were diagnosed as placenta accreta by ultrasonographic examination on admission to hospital. Elective surgery was done at 36-37 weeks. Mid line abdominal incision with upper segment uterine incision with plication of lowers uterine segment with transverse compression sutures. Results: We present a clinical trial for conservative management of placenta accreta in 25 cases with 19 cases [76%] successfully managed without hysterectomy. Conclusions: Conservative management of placenta accreta can be successfully performed in young age females desiring fertility.